Item response theory facilitated cocalibrating cognitive tests and reduced bias in estimated rates of decline. - Crane, Paul K; Narasimhalu, Kaavya; Gibbons, Laura E; Mungas, Dan M; Haneuse, Sebastien; Larson, Eric B; Kuller, Lewis; Hall, Kathleen; van Belle, Gerald (J Clin Epidemiol, 2008)
OBJECTIVE: To cocalibrate the Mini-Mental State Examination, the Modified Mini-Mental State, the Cognitive Abilities Screening Instrument, and the Community Screening Instrument for Dementia using item response theory (IRT) to compare screening cut points used to identify cases of dementia from different studies, to compare measurement properties of the tests, and to explore the implications of these measurement properties on longitudinal studies of cognitive functioning over time. STUDY DESIGN AND SETTING: We used cross-sectional data from three large (n>1000) community-based studies of cognitive functioning in the elderly. We used IRT to cocalibrate the scales and performed simulations of longitudinal studies. RESULTS: Screening cut points varied quite widely across studies. The four tests have curvilinear scaling and varied levels of measurement precision, with more measurement error at higher levels of cognitive functioning. In longitudinal simulations, IRT scores always performed better than standard scoring, whereas a strategy to account for varying measurement precision had mixed results. CONCLUSION: Cocalibration allows direct comparison of cognitive functioning in studies using any of these four tests. Standard scoring appears to be a poor choice for analysis of longitudinal cognitive testing data. More research is needed into the implications of varying levels of measurement precision.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Dementia; Disease Progression; Epidemiologic Methods; Female; Humans; Male; Neuropsychological Tests; Psychometrics